Recovery of mouth-opening after closed treatment of a fracture of the mandibular condyle: a longitudinal study. Issue 2 (February 2015) - Niezen, E.T.; Stuive, I.; Post, W.J.; Bos, R.R.M.; Dijkstra, P.U.
Abstract The aim of this retrospective study was to assess recovery of mouth opening after closed treatment of fractures of the mandibular condyle, and analyse which characteristics might influence recovery. We measured mouth opening in 142 patients (mean (SD) age 30 (14) years, 96 of whom were male) during follow-up at 3, 6, 13, 26, and 52 weeks after the injury. Fractures were assessed on radiographs. Data were analysed using a multilevel analysis. Half the fractures were of the low condylar neck (n = 71). Thirty-seven patients had bilateral condylar fractures, 29 had dislocated fractures, and in 80 the fracture was displaced. One or more additional mandibular fractures were present in 68. During follow-up mean (SD) mouth opening increased to: 33.6 (9.6) at 3 weeks, 40.1 (10.0) at 6 weeks, 45.1 (9.6) at 13 weeks, 49.8 (9.5) at 26 weeks, and 52.6 (7.5) at 52 weeks. Older age, female sex, displaced fracture, bilateral fractures, additional mandibular fractures, and the interaction between follow-up time and additional mandibular fractures, were predictors of a less favourable recovery of mouth opening. Clinicians can use the results of this study to predict recovery of mouth opening after closed treatment of fractures of the mandibular condyle at first consultation.